Kedudukan Hukum Anggota Koperasi sebagai Kreditor dalam Kepailitan Koperasi Simpan Pinjam - Najib A. Gisymar; Yessy Madya Putri (Universitas Sahid Surakarta, 2026)
This study examines the regulatory gap in bankruptcy petitions filed by cooperative members as creditors against savings and loan cooperatives as debtors, focusing on the legal standing of members in cooperative bankruptcy proceedings. The objective of this study is to identify, analyze, and evaluate the inconsistency between bankruptcy law and cooperative law in determining the legal standing of cooperative members who hold claims against their own cooperative. This study employs a normative juridical method using statutory, conceptual, and case approaches. The research data consist of primary legal materials, including statutory regulations and the Semarang Commercial Court decision concerning cooperative bankruptcy, as well as secondary legal materials, including literature, journal articles, and research findings from the undergraduate thesis that serves as the object of analysis. The findings indicate that members of savings and loan cooperatives occupy a complex legal position because they simultaneously act as members, owners, service users, and parties who may hold claims. This study concludes that Indonesian bankruptcy law has not yet provided an adequate normative construction regarding the position of cooperative members as creditors. Therefore, specific regulation is required to ensure legal certainty, member protection, and the proportional settlement of cooperative payment defaults.